Correlates of emotional intelligence among Iranian adolescents during the post pandemic era - Mousavi, Azadeh; Juhari, Rumaya; Kahar, Rojanah; Arshat, Zarinah (Faculty of Human Ecology, Universiti Putra Malaysia, 2023)
COVID-19 indeed had both positive and negative emotional impacts on adolescents, who grappled with challenging physical and mental changes. Some adolescents demonstrated resilience during the pandemic, adapting to the challenges and uncertainties they faced. Emotional intelligence, which involves recognizing and managing emotions, became crucial for adolescents undergoing significant physical and psychological changes during the pandemic. COVID-19 had adverse effects on the mental health of adolescents, leading to increased stress and emotional struggles. Measures such as social distancing negatively impacted adolescents' social interactions and emotional well-being. Moving forward to a post-pandemic world, it is essential to consider strategies for preventing or enhancing emotional intelligence among adolescents. Effective communication, whether with peers or parents, can equip adolescents with the emotional skills they need to transition into post-pandemic life and return to a sense of normality .These strategies can be informed by a deeper understanding of the emotional impact of COVID-19 on this demographic. This study tries to enhance emotional intelligence according to the Goleman Mixed Model(1995), The Theory of Attachment by Bowlbey (1983), and Social Information Process Theory by Crick and Dodge (1994). Data collected from 384 Iranian adolescents from Ahvaz aged between 15 to 18 years old, using a self-administered questionnaire that combined Emotional Intelligence Scale by Siberia Schering (1995),COVID-19 Impact Scale by Brome et al. (2020), Parent and Peer Attachments Scale by Armsden and Greenberg (1987), and Online Networking Scale by Soleymani (2016). The hypotheses were tested using the Statistical Package for the Social Sciences version 26 (SPSS). Accordingly, COVID19 (r=-.285,p<.05), maternal attachment (r=.217, p<.05), paternal attachment (r=.375, p<.05), peer attachment(r=.441, p<.05), and online networking (r=.141, p<.05), showed significant relationships with emotional intelligence among adolescents in Ahvaz, Iran. In conclusion, concerted efforts to enhance emotional intelligence among adolescents is essential in developing strategies that support their emotional well-being.